2015
DOI: 10.5307/jbe.2015.40.4.373
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Nanocrystals as Advanced "Green" Materials for Biological and Biomedical Engineering

Abstract: Background: Cellulose is a ubiquitous, renewable and environmentally friendly biopolymer, which has high promise to fulfil the rising demand for sustainable and biocompatible materials. Particularly, the recent progress in the synthesis of highly crystalline cellulose-based nanoscale biomaterials, namely cellulose nanocrystals (CNCs), draws significant attention from many research communities, ranging from bioresource engineering, to materials science and engineering, to biological and biomedical engineering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 141 publications
0
16
0
Order By: Relevance
“…Such a wide application spectrum is related mainly to their nanometer-sized features, large surface area, specific biomechanical characteristics, surface chemistry, ease of conjugation, high biocompatibility, and low (if any) cytotoxicity (Alexandrescu et al 2013) with tolerogenic potential to the immune system (Tomić et al 2016). Due to a general acceptance as˝biosafe˝nanomaterial (Č olić et al 2014;Tomić et al 2016), the cellulose nanocrystals (CNCs), with typical sizes of \300 nm in length and around 10 nm in diameter (Habibi et al 2010), have also been readily evaluated as catalysis (Zhou et al 2013) in biomedical engineering (Sinha et al 2015), as well as targeted drugs (Taheri & Mohammadi 2015) and gene (Hu et al 2015) delivery. Recent studies also demonstrated the potential of CNCs to target tumours via the Enhanced Permeability and Retention (EPR) effect and delivery of organic compounds or drugs into cancer cells (Drogat et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Such a wide application spectrum is related mainly to their nanometer-sized features, large surface area, specific biomechanical characteristics, surface chemistry, ease of conjugation, high biocompatibility, and low (if any) cytotoxicity (Alexandrescu et al 2013) with tolerogenic potential to the immune system (Tomić et al 2016). Due to a general acceptance as˝biosafe˝nanomaterial (Č olić et al 2014;Tomić et al 2016), the cellulose nanocrystals (CNCs), with typical sizes of \300 nm in length and around 10 nm in diameter (Habibi et al 2010), have also been readily evaluated as catalysis (Zhou et al 2013) in biomedical engineering (Sinha et al 2015), as well as targeted drugs (Taheri & Mohammadi 2015) and gene (Hu et al 2015) delivery. Recent studies also demonstrated the potential of CNCs to target tumours via the Enhanced Permeability and Retention (EPR) effect and delivery of organic compounds or drugs into cancer cells (Drogat et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The development of a thermooptical element has been modeled theoretically, and involves modification of a transparent solid with thin layers which absorb excitation radiation . Based on the calculation method, the photothermal response of the sample was found to exhibit linear dependence on the total absorption of the surface layer, and this allowed for thermophysical interpretation of the results in terms of both the material and the spectrometer . It has been found that PAS signal increases significantly for species absorbed on cellulose or wood .…”
Section: Outlooks For Photothermal Characterization Of Cellulose and mentioning
confidence: 99%
“…Recently, a great deal of attention has been directed towards the development of novel cost-effective tissue-mimicking composites using natural materials and green approaches of their engineering [14]. Nanocellulose, generally classified as either highly crystalline (54-88%) cellulose nanocrystals (CNCs) or semicrystalline cellulose nanofibrils (CNFs), derived from plant biomass, marine animals, or microbial/bacterial sources [15][16][17][18], has been thus also confirmed as promising for various biomedical applications [19,20], due to its large surface area, good biomechanical properties (Young's modulus up to~145 GPa and mechanical strength up to~7500 MPa), abundant hydroxyl groups for potential functionalization, high biocompatibility [21], and insignificant cytotoxicity [22] within the tolerance limit of an immune system [23,24]. Relatively more flexible CNFs with a few micrometer in length and up to 150 nm in diameter have been explored extensively in wound healing [25], tissue engineering [26], and cell therapy [27], while smaller and more rigid CNCs with <300 nm in length and around 10 nm in diameter were used as targeted drugs [28][29][30][31] and genes [32] in delivery systems and in diagnostics [33].…”
Section: Introductionmentioning
confidence: 99%